The implementation of maintenance works for historical buildings – A review on the current scenario - Abdul Rashid, Robiah; Ahmad, A. Ghafar (2008)
The conservation of historical buildings is a method on preserving structures which are historically and culturally important to the nation. Conservation involves works undertaken to preserve the condition of the building to its original state and this also includes the subsequent maintenance works. Maintenance is identified as a means on prolonging the lifespan of the historical structures. Without proper and systematic maintenance works, without doubt, the historical buildings will deteriorate and becoming dysfunctional as well as unfit to be used. This paper intends to highlight the establishment of maintenance management, the responses on the importance of maintenance works to be undertaken for historical buildings, factors governing the effectiveness of maintenance works on historical buildings and maintenance approaches, inclusive of maintenance programmed undertaken on the structural, non-structural elements as well as the services systems. The findings for this research are summarized from the responses obtained directly from the respondents employed for the management of the historical buildings. Case studies involving 20 numbers of historical buildings, of which some are already categorized under national heritage, were carried out. The methodology for this research is based on personal interviews and distribution of self-developed questionnaire which consists of 10 key topics, all developed relating to conservation of historical buildings and the current scenario on the implementation of maintenance works on these buildings.